A comparative study on the knowledge, attitudes, and practices of self-medication in rural and urban regions of Tumkur, Karnataka, India - Challa K. Supriya; Chaitanyaa Prakash; Thimmegowda Nandini; Pesala Pavan Kumar Reddy (MGM Journal of Medical Sciences)
Background: Self-medication (SM), defined as using medicines without professional medical advice, is an increasing public health concern, particularly in developing countries like India. This study aimed to evaluate and compare SM practices among residents of rural and urban areas of Tumkur, Karnataka, India. Materials and Methods: A cross-sectional survey was conducted to assess and compare the knowledge, attitudes, and practices regarding SM among rural and urban populations in Tumkur. Two hundred individuals participated, equally divided between 100 from rural areas and 100 from urban areas. Data were gathered using a structured and pre-tested questionnaire that included sections on demographic details, medication usage patterns, and perceptions about SM. The collected data were analyzed using Jeffreys’s Amazing Statistics Program. Results: SM was prevalent in both rural and urban areas. Urban residents (28.5%) demonstrated higher awareness, with 32.5% frequently reading package inserts, and reported slightly more adverse effects (9%). Both groups commonly used SM for conditions such as headaches (31.5%), fever (26.5%), and cough (20.5%). Rural participants (24.5%) showed a higher acceptance of SM. Pharmacies were the primary source of medication for both groups, with 48.5% of rural participants and 39% of urban participants obtaining their medicines from pharmacies. Conclusion: This study uniquely compares SM practices in rural and urban areas, highlighting regional differences. The findings indicate the necessity of strengthening the role of pharmacists, enforcing stricter regulations on over-the-counter medications, and improving healthcare access, especially in rural areas.